Portfolio Flows into Indonesia: Push or Pull? - Chaikal Nuryakin; Edith Zheng Wen Yuan; I Gede Putra Arsana (Economics and Finance in Indonesia, 2016)
This paper focuses on the dynamic of the portfolio flows into Indonesia. The result of Structural Vector Autoregression (SVAR) model reveals that push factors is more dominant than pull factors in explaining portfolio flows into Indonesia. Portfolio flows into Indonesia are positively correlated with regional’s stock market performance and negatively correlated to the federal funds rate. On the pull factors, domestic risk (the Credit Default Swap spread) is more dominant than domestic return (the BI rate) in explaining the flows. Thus, it is important for authorities to have more focus on domestic risk–relative to rate of return–in managing portfolio flows. In addition, the negative impact of the lagged Indonesia stock market index to the capital flows indicates a counter cyclical investment behavior of global investors. AbstrakStudi ini mengkaji dinamika arus investasi portofolio Indonesia. Hasil dari model Structural Vector Autoregression (SVAR) menunjukkan bahwa "faktor pendorong" lebih dominan dibandingkan "faktor penarik" dalam menjelaskan pergerakan arus investasi portofolio. Arus investasi portofolio ini berkorelasi positif dengan kinerja pasar saham regional dan berkorelasi negatif dengan tingkat suku bunga the Fed. Untuk faktor penarik, risiko domestik (CDS) menjadi faktor yang dominan dibandingkan imbal hasil (BI rate) yang menguatkan pentingnya manajemen risiko perekonomian domestik dalam stabilisasi arus investasi portofolio. Lebih lanjut, studi ini juga mengindikasikan adanya perilaku kontra siklikal dari investor global.Kata kunci: Arus Investasi Portofolio; SVARJEL classifications: F32; G11